FORMATION OF CREATIVE ACTIVITY OF STUDENTS IN THE STUDY OF GRAPHIC EDITORS IN THE SEWING INDUSTRY - Grinev, Dmitry; Eliseyeva, Natalya; Ivanova, Daria (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2018)
The article presents the psychological, pedagogical and methodical aspects of the development of students' creative activity. Examples of creative assignments when studying graphic editors in the sewing industry are presented.